2020
DOI: 10.1111/jfpp.14598
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propolis and nisin on Listeria monocytogenes in contaminated ice cream

Abstract: Foodborne illness and deaths caused by pathogenic microorganisms have become important public health concerns in recent years.Dangerous pathogens can easily contaminate foods and cause foodborne diseases. Ready-to-eat products like salad and ice cream are especially vulnerable and can cause foodborne diseases because these foods are not exposed to any further treatments before consumption to eliminate dangerous microorganisms. The nutritional value of ice cream is high due to its milk content. Therefore, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a study evaluating the antimicrobial effect of propolis-added ice cream, it was observed that the addition of propolis did not significantly affect the first dripping time and melting rate results. In the study, the first dripping times were found to be between 421s-459s, and the melting rate was found to be between 16.4% and 16.7% (Demir Özer, 2021). The values in this study were found to be higher than these values and this difference is thought to be due to the changes in ice cream formulations.…”
Section: Determination Of First Dripping Time and Melting Ratementioning
confidence: 47%
“…In a study evaluating the antimicrobial effect of propolis-added ice cream, it was observed that the addition of propolis did not significantly affect the first dripping time and melting rate results. In the study, the first dripping times were found to be between 421s-459s, and the melting rate was found to be between 16.4% and 16.7% (Demir Özer, 2021). The values in this study were found to be higher than these values and this difference is thought to be due to the changes in ice cream formulations.…”
Section: Determination Of First Dripping Time and Melting Ratementioning
confidence: 47%
“…As nisin is the sole bacteriocin approved as a food preservative [ 13 ], various approaches have been made to better control L. monocytogenes by further potentiating nisin. Several compounds have been reported to generate antimicrobial synergy in combination with nisin against L. monocytogenes , including propolis [ 17 ], citric acid [ 24 ], sodium diacetate [ 43 ], perilla oil [ 44 ], and grape seed extract [ 45 ]. Based on our previous studies on the antimicrobial synergy of gallic acid derivatives in other Gram-positive pathogens [ 25 , 26 , 27 , 28 ], we examined whether gallic acid and its derivatives could enhance the activity of nisin against L. monocytogenes, and discovered that gallic acid increases the antibiofilm activity of nisin ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nisin is highly effective against Gram-positive bacteria, including Listeria , Staphylococcus , Clostridium , and Bacillus , by forming pores in the membrane and inhibiting cell wall synthesis through binding to lipid II [ 14 , 15 ]. Because of its potent antimicrobial activity, nisin has been used by the food industry to control L. monocytogenes in dairy, meat, and canned products [ 16 , 17 , 18 ]. In addition, nisin has been reported to inhibit the growth of other species of Listeria in combination with some natural organic compounds, including carvacrol, eugenol, cinnamic acid, and thymol [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propolis bioactivity on Listeria spp. and L. monocytogenes (bacillus g(+)) has been studied by some authors in some meat, dairy, vegetable, and fruit products [ 10 , 11 , 12 ]. Given the organoleptic characteristics of propolis (potent aroma and intense color), it is necessary to determine low effective doses in its application to food products [ 3 ].…”
Section: Introductionmentioning
confidence: 99%